Roaming among humans: noteworthy records of jaguar (Panthera onca) close to human settlements in the Paraguayan Humid Chaco - R. Laino; K. Musalem; A. Weiler; J. F. González–Maya (Arxius de Miscel-lània Zoològica)
Deambulant entre éssers humans: registres notables sobre el jaguar (Panthera onca) prop d’assentaments humans al Chaco Humit del Paraguai